Estimation of starvation and diet variation of the RNA/DNA ratios in field-caught Sardina pilchardus larvae off the north of Spain - Chicharo, Alexandra (1998)
The aim of this study was to analyse the general larval condition, to determine the lncidence of starvation and to investigate the effect of time of day on RNA/DNA ratios among field-caught Sardina pilchardus (L.) larvae. The larvae were collected during 4 research cruises off northern Spain, during March, April, May and June 1992. A highly sensitive fluorometric method for nucleic acid quantification was applied to larvae of S. pilchardus. The means of the RNA/DNA ratio were relat~vely high, so the larvae collected off northern Spain were generally in good condition. Low percentages of starving larvae (RNA/DNA ratio less than 1.3), ranging from 0 to 3.23%, were found over the 4 mo. The RNA/DNA ratios were significantly correlated with zooplankton biomass. Larvae collected at night revealed higher RNA/DNA ratios compared to larvae caught during the day. This seems to indicate that there is some endogenous rhythm in the production of RNA. It would then follow that, if there are die1 changes in RNA concentrations, average RNA Indices can be unrepresentative if there IS any day/night bias in sampling.